LA FUNCIÓN PRAGMÁTICA DEL ACENTO EN LA EXPRESIÓN DE LA EMOCIÓN - Narbona Reina, Beatriz (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract The aim of this paper is the study of the interactive character of language from a pragmatic perspective. Given that objective, suprasegmental stress placement is studies as a way to express emotions in English language spoken discourse. Because of the complexity of the theme, this study will be based on psychological and linguistic contributions (taking into account phonetic and pragmatic perspectives).To get empirical results, the analysis of stress placement is based on real data, taken from five TV interviews from CNN. These programs, recorded on videotape, and involve different native English speakers treating diverse themes. The results show that suprasegmental stress is an important device when dealing with emotions. Its location and density reinforces or highlights different semantic or pragmatic contents, revealing itself as a necessary tool in the case of emotive communication.